AIAA Scitech 2019 Forum 2019
DOI: 10.2514/6.2019-1524
|View full text |Cite
|
Sign up to set email alerts
|

Topology Optimization of Composite Self-Deployable Thin Shells with Cutouts

Abstract: The paper presents topology optimization studies of selfs-deployable joints in thin-walled tubular structures. The joints are made entirely of ultra-thin, fiber reinforced composite materials. The objective of this research is to strategically position cutouts on the joints so that they can fold without failing, while maximizing the deployed bending stiffness. The optimal shape and position of cutouts are the results of concurrent topology optimization of these composite, thin-shell joints with geometrical non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Seffen and Pellegrino [213] reported that this case of loading promotes the deployment to occur along the same path, increasing the repeatability of the process. Later research [26,80,148,151,184,206,225,231,264,281], more focused on composite materials, further supports the results obtained on the behaviour of tape-springs and on the use of torque-angle curves to characterize the retraction of tape-springs, leading to their application in several studies.…”
Section: Experimental Characterization Of Deployable Tape-springsmentioning
confidence: 68%
See 3 more Smart Citations
“…Seffen and Pellegrino [213] reported that this case of loading promotes the deployment to occur along the same path, increasing the repeatability of the process. Later research [26,80,148,151,184,206,225,231,264,281], more focused on composite materials, further supports the results obtained on the behaviour of tape-springs and on the use of torque-angle curves to characterize the retraction of tape-springs, leading to their application in several studies.…”
Section: Experimental Characterization Of Deployable Tape-springsmentioning
confidence: 68%
“…More recently, Ferraro and Pellegrino (2019) [80] explored the use of a topology optimization approach to define the geometry of the cut-outs in a composite deployable corner joint. The adopted topology optimization method differs from the original concept proposed by Bendsøe and Kikuchi in 1988 [23], where the element of a material volume had their density changed depending on a given criteria (such as maximizing the stiffness).…”
Section: Design Of Composite Deployable Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the characteristic shell dimension increases, gravity (and its associated loading) becomes a hindrance to the adoption of thin shells as compliant mechanisms at the larger scales-the physical limit of compliance in the scaling of thin shells is found to be around 0.1 m.Biomimetics 2020, 5, 4 2 of 18 describe the large shape transitions of viruses [8], and of red blood cells [9], and are the mechanical system for some of the fastest repeatable plant movements [1]. Their flexibility allows the movement in engineered compliant structures such as hingeless joints [10], or active piezoelectric actuators [11]. All these flexible structures are elastically deformed, which makes them susceptible to undergo large stresses.…”
mentioning
confidence: 99%